Portuguese Physical Literacy Assessment - Observation (PPLA-O) for adolescents (15-18 years) from grades 10-12: Development and initial validation through item response theory - João Mota; João Mota; João Mota; João Martins; João Martins; Marcos Onofre; Marcos Onofre (Frontiers Media S.A., 2022)
IntroductionAims of these studies were to develop the Portuguese Physical Literacy Assessment Observation instrument (PPLA-O) to assess the physical and part of the cognitive domain of Physical Literacy (PL) through data collected routinely by Physical Education (PE) teachers; and to assess the construct validity (dimensionality, measurement invariance, and convergent and discriminant validity) and score reliability of one of its modules [Movement Competence, Rules, and Tactics (MCRT)].MethodsContent analysis of the Portuguese PE syllabus and literature review were used for PPLA-O domain identification. Multidimensional Item Response Theory (MIRT) models were used to assess construct validity and reliability, along with bivariate correlations in a sample of 515 Portuguese grade 10-12 students (Mage = 16, SD = 1).ResultsPPLA-O development resulted in an instrument with two modules: MCRT (22 physical activities) and Health-Related Fitness (HRF; 5 protocols); both assessed with teacher-reported data entered in a spreadsheet. A two correlated dimensions Graded Response Model (Manipulative-based Activities [MA], and Stability-based Activities [SA]) showed best fit to the MCRT data, suggesting measurement invariance across sexes, and adequate to good score reliabilities (MA = .89, and SA = .73). There was a moderate to high correlation (r = .68) between dimensions, and boys had higher scores in both dimensions. Correlations among MCRT scores and HRF variables were similar in magnitude to previous reports in meta-analysis and systematic reviews.ConclusionsPPLA-O is composed of two modules that integrate observational data collected by PE teachers into a common frame of criterion-referenced PL assessment. The HRF module uses data collected through widely validated FITescola® assessment protocols. The MCRT makes use of teacher-reported data collected in a wide range of activities and movement pursuits to measure movement competence and inherent cognitive skills (Tactics and Rules). We also gathered initial evidence supporting construct validity and score reliability of the MCRT module. This highly feasible instrument can provide Portuguese grade 10-12 (15-18 years) PE students with feedback on their PL journey, along with the other instrument of PPLA (PPLA-Questionnaire). Further studies should assess inter and intra-rater reliability and criterion-related validity of its two modules.